Measurement of Radon Concentrations and Annual Dose Rate in some Regions of Baghdad City using LR-115 Nuclear Track Detector - Salih, Lutfi Majeed Mohammed (Al-Nahrain Journal of Science, 2018)
In this work, LR-115 solid state nuclear track detector used to measure the indoor and outdoor radon concentrations, the annual absorbed dose rate and annual effective dose rate to the lung, were measured in nine houses at different places of Baghdad city, the observed values of indoor and outdoor radon concentrations was in range of 14.7-46.17 Bq/m3 and 9.69–35.69 Bq/m3 respectively. The resulting concentration of Short-lived radon daughters expressed in term of an equilibrium-equivalent radon concentration (EEC), the minimum and maximum indoor results of (EEC) was 5.88-18.46 Bq/m3 and the outdoor results was 6.78-24.98 Bq/m3. The Potential Alpha Energy (PAE) concentration expressed in Working Level (WL) units was in the range of 1.58-4.99 mWL in indoor and 1.8-6.75 mWL in outdoor regions. The annual effective dose calculated according to the radiation weighting (WR) factor for alpha particles and the tissue weighting (WT) factor and the annual absorbed dose rate, the present results confirmed that the radon gas concentrations in all the nine places of Baghdad city are lower than the International Commission Radiation Protection (ICRP) agency, recommended value (200Bq/m3).